Publication rates of presentations given at annual conferences of The Wildlife Society, 1994–2006. (11th December 2013) - McRoberts, Jon T.; Ferguson, Adam W.; Schwalm, Donelle L.; Timmer, Jennifer M.; Ballard, Warren B.
ABSTRACT Annual conferences of The Wildlife Society (TWS) are important venues to advance wildlife science research through the presentation of papers and posters. However, no longitudinal analysis has been conducted of publication rates of TWS conference presentations. We classified all conference presentations from 1994 to 2006 by publication status, publication outlet, lead author affiliation, and elapsed time between presentation and publication to analyze presentation and publication trends. Of the 6, 279 presentations reviewed, 1, 771 were published (28.2%), primarily in the Journal of Wildlife Management (22.9%) or the Wildlife Society Bulletin (15.2%). The average time between presentation and publication was 30.1 ± 0.6 months. Academics provided most of the presentations (52.6%), as well as publications (62.4%). We believe consideration of TWS annual conference presentation and publication metrics by TWS membership and conference organizers is warranted to ensure maximum stakeholder benefit. We discuss these implications of publication analysis and offer suggestions for increasing publication rates, if that becomes a goal of TWS. We encourage periodic investigation to quantify conference benefits and to better assess the efficacy of TWS conferences. © 2013 The Wildlife Society.